Co-production dimensions in medical services - Emily Hon Tshin Yapp; Stephen Sondoh J.R; Ruth Siganul (International Institute of Social and Economic Sciences (IISES), 2015)
Previous research has shown that customer co-production is able to improve company’s productivity, enhance customer loyalty, increase competitiveness and enhance customer satisfaction. Although customer co-production has long been recognized in the service marketing literature, few empirical studies examine the dimensions of co-production in medical services. In addition, services providers in the industry are competing with each other to find ways to get closer to the organizations. A closer relationship between customers and organization could enhance competitive advantage and enable more profitable relationship. Therefore, the present study aims to identify factors (affective commitment, communications, interaction justice and patient expertise) that can effectively enhance the level of customer co-production. Survey questionnaires are distributed using individually completed questionnaires in a set of 24 items. Each item was phrased as statement on 5-points Likert scales. These 5-points Likert scales type scales with anchor ranging from strongly disagree to strongly agree. The respondents are the undergraduate students at a public university in Malaysia. The surveyed data are analyses using the Partial Least Squares (PLS) approach. The survey results suggest that interactional justice, communication and patient's expert can increase the level of co-production. This implied that patients and doctor communication could lead to an effective understanding of each other’s role during the co-production process and the outcome. In addition, the finding also shown that interaction justice had a significant and positive association with co-production. This suggested that the emotional of relationship between patient and doctor is also an interest in customers in order to participate in co-production. As for patients' expertise, it seems that when patients have sufficient knowledge about their illness/disease, they are more likely to participate in co-production. Interestingly, affective commitment does not contribute to customer co-production. Limitation and future research directions are also discussed.